2012
DOI: 10.7314/apjcp.2012.13.2.511
|View full text |Cite
|
Sign up to set email alerts
|

p53 Exon 4 (codon 72) Polymorphism and Exon 7 (codon 249) Mutation in Breast Cancer Patients in Southern Region(Madurai) of Tamil Nadu

Abstract: Background: We investigated the association between polymorphisms in the p53 tumor suppressor gene and breast cancer risk in women especially in the Southern part of India. Methods: Genotyping was performed for 50 breast cancer women and 50 controls to determine the status of p53 exon 4 codon 72 polymorphism and exon 7 codon 249 mutation and their possible role in breast cancer risk. Results: Frequency of Arg/Arg at codon 72 was 18% in controls and 28% in patients, Arg/Pro frequency was 56% and 66% , Pro/Pro g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 23 publications
1
13
0
Order By: Relevance
“…Several polymorphisms have been identified in coding and noncoding regions of p53 that some of them have been associated with increased risk of cancer (Whibley et al, 2009). Three p53 well studied functional polymorphisms include Arg/Pro polymorphism in exon 4, 16 bp duplication in intron 3 (PIN3) and intron 6 G13964C alteration (Guleria et al, 2012), although two studies in India showed no link between polymorphisms and breast cancer (Roy et al, 2012;Vijayaraman et al, 2012) It has been reported that the 16 bp duplication in intron 3 is correlated with a reduced level of p53 mRNA and decreased both DNA repair capacity and apoptotic indices in lymmphoblastoid cell lines (Wu et al, 2013;Gemignani et al, 2004). Recently, several meta-analyses have highlighted the association between PIN3 and increased risk of cancer predisposition (Hu et al, 2010;He et al, 2011;Sagne et al, 2013;Wu et al, 2013).…”
Section: Lack Of Association Ofmentioning
confidence: 99%
“…Several polymorphisms have been identified in coding and noncoding regions of p53 that some of them have been associated with increased risk of cancer (Whibley et al, 2009). Three p53 well studied functional polymorphisms include Arg/Pro polymorphism in exon 4, 16 bp duplication in intron 3 (PIN3) and intron 6 G13964C alteration (Guleria et al, 2012), although two studies in India showed no link between polymorphisms and breast cancer (Roy et al, 2012;Vijayaraman et al, 2012) It has been reported that the 16 bp duplication in intron 3 is correlated with a reduced level of p53 mRNA and decreased both DNA repair capacity and apoptotic indices in lymmphoblastoid cell lines (Wu et al, 2013;Gemignani et al, 2004). Recently, several meta-analyses have highlighted the association between PIN3 and increased risk of cancer predisposition (Hu et al, 2010;He et al, 2011;Sagne et al, 2013;Wu et al, 2013).…”
Section: Lack Of Association Ofmentioning
confidence: 99%
“…Similarly, no association between TP53 codon 72 variants and breast cancer risk was observed in Japanese (Kawajiri et al, 1993), Pakistani (Khaliq et al, 2000), Tunisian (Mabrouk et al, 2003), Finnish (Tommiska et al, 2005), Iranian (Khadang et al, 2007), Brazilian (Vieira et al, 2008) and South Indian populations (Suresh et al, 2011;Vijayaraman et al, 2012). Contrary to our results, association between RR genotype and breast cancer risk have been reported in Turkish (Buyru et al, 2003), Italian (Bonafe et al, 2003), Jewish (Ohayon et al, 2005), Greek (Papadakis et al, 2000;Kalemi et al, 2005), Brazilian (Damin et al, 2006;Aoki et al, 2009) and Chinese (Ma et al, 2006) population.…”
Section: Discussionmentioning
confidence: 99%
“…A lot of studies have been conducted to evaluate the role that these three genotypes play in breast cancer worldwide and have reported different results in this field. For example, the studies of Khadang et al,13 Kazemi et al,14 and Agorastos et al15 in Greece and Vijayaraman et al16 in southern part of Maduria found no significant relationship between polymorphism of this codon in p53 gene and breast cancer. In contrast, the studies of Sheikhpour and Zahir17 and Golmohammadi and Namazi18 showed a significant relationship.…”
Section: Introductionmentioning
confidence: 98%